Delayed Degradation and Impaired Dendritic Delivery of Intron-Lacking EGFP-Arc/Arg3.1 mRNA in EGFP-Arc Transgenic Mice - Steward, Oswald; Matsudaira Yee, Kelly; Farris, Shannon; Pirbhoy, Patricia S.; Worley, Paul; Okamura, Kohji; Okuno, Hiroyuki; Bito, Haruhiko (Frontiers in Molecular Neuroscience, 2018)
Arc is a unique immediate early gene (IEG) whose expression is induced as synapses are modified during learning. Newly-synthesized Arc mRNA is rapidly transported throughout dendrites and localizes near recently activated synapses. Arc mRNA levels are regulated by rapid degradation, which is accelerated by synaptic activity in a translation-dependent process. One possible mechanism is nonsense-mediated mRNA decay (NMD), which depends on the presence of a splice junction in the 3’UTR. Here, we test this hypothesis using transgenic mice that express EGFP-Arc. Because the transgene was constructed from Arc cDNA, it lacks intron structures in the 3’UTR that are present in the endogenous Arc gene. NMD depends on the presence of proteins of the exon junction complex (EJC) downstream of a stop codon, so EGFP-Arc mRNA should not undergo NMD. Assessment of Arc mRNA rundown in the presence of the transcription inhibitor actinomycin-D confirmed delayed degradation of EGFP-Arc mRNA. EGFP-Arc mRNA and protein are expressed at much higher levels in transgenic mice under basal and activated conditions but EGFP-Arc mRNA does not enter dendrites efficiently. In a physiological assay in which cycloheximide (CHX) was infused after induction of Arc by seizures, there were increases in endogenous Arc mRNA levels consistent with translation-dependent Arc mRNA decay but this was not seen with EGFP-Arc mRNA. Surprisingly, however systemic delivery of CHX did not lead to increases in Arc mRNA that have been seen in rats, suggesting that this mechanism of Arc mRNA degradation does not play a major role with behavioral induction in mice. Taken together, our results indicate: 1) Arc mRNA degradation occurs via a mechanism with characteristics of NMD; 2) rapid dendritic delivery of newly synthesized Arc mRNA after induction may depend in part on prior splicing of the 3’UTR.